United States Jewry, 1776-1985 Volume 2, The Germanic Period - Rader Marcus, Jacob (Wayne State University Press, 2018)
In United States Jewry, 1776-1985, the dean of American Jewish historians, Jacob Rader Marcus, unfolds the history of Jewish immigration, segregation, and integration; of Jewry's cultural exclusiveness and assimilation; of its internal division and indivisible unity; and of its role in the making of America. Characterized by Marcus's impeccable scholarship, meticulous documentation, and readable style, this landmark four-volume set completes the history Marcus began in The Colonial American Jew, 1492-1776. The second volume of this seminal work on American Jewry covers the period from 1841 to 1860. Unlike the early Jewish settlers, these immigrants were Ashkenazim from Europe's Germanic countries. Marcus follows the movement of these "German" Jews into all regions west of the Hudson River.